Rapport Management in President Buhari and Governor Sanwo-Olu’s Speeches on #EndSARS Protest in Nigeria - Akinwotu, Samuel Alaba (International Journal of Language and Literary Studies, 2021)
Speech making in politics is an essential tool used to manage relationships between politicians and the electorate. The success of a speech depends on the content and the discourse and linguistic strategies employed to achieve speakers’ communicative goals. Political speeches have been widely studied, but extant studies have given tangential attention to the management of rapport in speeches of political office holders delivered in crisis situation in Nigeria. Two speeches delivered by President Muhammadu Buhari (PMB) and Governor Babajide Sanwo-Olu (GBS) on the #EndSARS protests in Nigeria, downloaded from www.guardian.ng and www.premiumtimesng.com respectively, were purposively selected and analysed using Rapport Management theory. This is with the view to accounting for the linguistic elements and discourse strategies and their functions in maintaining harmonious relationship in selected texts. Linguistic elements such as the inclusive “we”, the institutional “I”, collective/possessive “us” “our” “your” and descriptive adjectives and strategies such as claiming common ground, expressing solidarity, showing empathy were employed to manage rapport and achieve communicative goals by PMB and GBS. While GBS tactically avoids utterances that are rapport threatening, some utterances of PMB have the tendency to impair rapport. He however mitigates them through hedging, personalisation, institutionalisation and testimonial argument.